Model Peningkatan Pemanfaatan Sistem Informasi Rumah Sakit Berdasarkan Metode HOT-Fit di RSPI Prof. Dr. Sulianti Saroso - Anang Suryana; Fransiskus Adikara; MF Arrozi; Akhmad Taufik (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
Hospital management requires fast and accurate data management in order to create quality services. Evaluation of an information system is needed to find out the actual condition of system operation so that the achievement of evaluation activities will improve performance in its application. In this essay, Evaluation using the HOT-Fit method which was developed with elements of knowledge and regulation is effective in evaluating the information system. This study aims to analyze the influence of human, organization, technology, knowledge and regulation on benefits, either simultaneously or partially. This study uses quantitative research methods with the type of research is causality explanatory. The analytical method used is multiple linear regression analysis. Respondents in this study were the respondents of RSPI Prof. Dr. Sulianti Saroso who operates SIMRS directly as many as 154 employees. The results of this study indicate that there is a significant influence from Human, Organization, Technology, Knowledge, and Regulations that affect the benefits of 80.9%. Human, Organization, Technology, Knowledge, and Regulation partially affect the benefits, with the provisions of the regulation being the variable that has the highest influence benefits. Regulation is the most dominant variable affecting the benefits of using SIMRS. It is necessary to improve the quality of SIMRS services related to regulations so that the hospital remains consistent in using quality developers who understand all business processes in hospitals.